Ethyl (Z)-2-chloro-2-[2-(4-methoxyphenyl)hydrazin-1-ylidene]acetate - Asiri, Abdullah M. (International Union of Crystallography, 2012)
The molecule of the title compound, C(11)H(13)ClN(2)O(3), is planar (r.m.s. deviation = 0.0587 Å for non-H atoms) and adopts a Z conformation about the C=N double bond. In the crystal, molecules are linked via an N—H⋯O hydrogen bond, forming zigzag chains propagating along [010]. These chains are consolidated by C—H⋯O hydrogen bonds.